The Effect of Storage Temperature on Organoleptic and Physical Quality on Salted Smoked Eggs - Wati, Anif Mukaromah; Muarifah, Hanum; Herlambang, Chanifan Ibadi Fajar; Pratama, Heaven Nila Nanda; Azizah, Siti (Universitas Halu Oleo, 2022)
ABSTRACT The purpose of this study was to determine the quality of salted smoke eggs which were stored at different storage temperatures of their physical and organoleptic qualities. The materials used in making salted smoke eggs are duck eggs, salt, bricks, and water. Methods of making the products are covering eggs with pasta or coating method, boiling eggs carefully, and smoking salted eggs until they are brown. Eggs are stored at different temperatures for 7 days including Storage at 5°C (refrigerator), Storage at 22°C (air conditioning), storage at ±28oC (room temperature), and Storage at 35°C (incubator). The results showed that salted smoke eggs stored at different temperatures had a significant effect (P<0.05) on taste and appearance but had no significant effect on aroma and air cavity. The conclusion of this study is that smoked salted smoke eggs with 7 days of storage are better if stored at incubator temperature and room temperature because, in 7 days of storage there has been no change in organoleptic quality.Keywords: different temperature, organoleptic quality, physical quality, salted smoke eggs